The Effect of Resorcinol on Bovine Spermatozoa Parameters in Vitro - Massányi, M; Halo, M; Strapáková, L; Slanina, T; Ivanič, P; Strapáková, E; Strapák, P; Halo, M; Greń, A; Formicki, G; Massányi, P (Physiological research, 2020)
The goal of this study was to observe the effect of resorcinol on motility, viability and morphology of bovine spermatozoa. The semen was used from six randomly chosen breeding bulls. Ejaculate was diluted by different solutions of resorcinol in 1:40 ratio. Samples were divided into 7 groups with different concentrations of resorcinol (Control, RES1 - 4 mg/ml, RES2 - 2 mg/ml, RES3 - 1 mg/ml, RES4 - 0.5 mg/ml, RES5 - 0.25 mg/ml and RES6 - 0.125 mg/ml). Motility of spermatozoa was detected using CASA method at temperature of 37 °C in time periods 0, 1, 2, 3, 4 hours from the start of the experiment. Significant motility differences between all groups except control and RES6 with difference of 5.58 %, as well as between RES1 and RES2 groups with difference of 2.17 % were found. Progressive motility had the same significant differences. Spermatozoa viability (MTT test) decreased compared to control in all experimental groups during the entire duration of experiment. Observing morphologically changed spermatozoa, no significant changes were observed and a higher percentage of spermatozoa with separated flagellum in all experimental resorcinol groups compared to control were detected. Also, increased number of spermatozoa with broken flagellum, acrosomal changes and other morphological forms in the group with the highest concentration of resorcinol (RES1) were found. Results of our study clearly show negative effects on motility parameters of spermatozoa which depend on concentration, cultivation temperature and time period.
Keywords: skot; spermie; Cattle; sperma; techniky in vitro; resorcinoly; vztah mezi dávkou a účinkem léčiva; Male; Resorcinols; Semen; Animals; Spermatozoa; mužské pohlaví; Dose-Response Relationship, Drug; Sperm Motility; zvířata; In Vitro Techniques; motilita spermií